Health care spending structures in Poland, Latvia, Lithuania and Estonia over the years as compared to other EU countries - Renata Walczak; Marlena Piekut; Magdalena Kludacz-Alessandri; Biruta Sloka; Ligita Šimanskiene; Tiiu Paas (Foundations of Management, 2018)
After joining the European Union in 2004, the post-communist countries have dramatically changed their structure of expenditure for medical services. The cause of this is legislative and ownership changes in the new economy. The study analyzed the expenditure on medical services in the European Union with a special focus on Poland, Latvia, Lithuania and Estonia. The European Union countries were divided into clusters using different methods, that is, Ward's, Two Step and Centroid Clustering. In the paper, the structure and changes in health expenses were presented according to the types of expenditures over the years 2004-2015. Countries were assigned to clusters based on three variables: medical products, appliances and equipment, outpatient services and hospital services. Variables were considered as a percentage of household budget. In Lithuania, Latvia and Estonia, there is a clear increase in the outpatient services spending compared to the hospital services expenditure.
Keywords: H44; I11; 650; consumption; households; health; structure of expenditures